Affixation in The Rai Dialect of Kaili - Desman Christofel Pa'esa; Lundu Apriyani; Ni Komang Trisulasih; Birgita Rombe Tandioga (Civiliza Publishing, Indonesia., 2026)
One of the regional languages that is part of Indonesia's linguistic wealth is the Kaili language spoken by the people in Central Sulawesi. This study aims to describe the use of nominal, verbal, adjectival, and adverbial affixes in the syntactic constructions of the Rai Dialect of the Kaili Language. The study is motivated by the importance of understanding the relationship between affixation processes and the syntactic functions of words in sentence formation. This research employed a descriptive qualitative method with a syntactic approach. Data were collected through interviews, observations, and documentation of native speakers’ utterances. The findings indicate that nominal, verbal, adjectival, and adverbial affixes play significant roles in determining syntactic functions such as subjects, predicates, objects, complements, and adverbials. Affixation not only influences word categories but also contributes to the relationships among sentence constituents. The results of this study are expected to enrich syntactic studies of regional languages, particularly the Rai Dialect of Kaili, and support efforts to document and preserve local languages in Indonesia.